Tratamiento diferenciado de la fuerza pública en la jurisdicción especial para la paz (2017)
The present article seeks to differentiate the treatment of the agents of the State in the implementation of the agreement and the intervention of the International Criminal Court in the amnesty that was given in the same, being a research qualitative is taken as the reference positions of authors in order to describe how phenomenological characteristics of the subject in question, in this way, through the inductive method seeks to understand the implementation of the agreement and its amnesty Law in reality. It is then, that the legal classification of the legislative acts in the framework of the implementation of the Peace agreements in Colombia, is not concrete at the moment of defining whether the differentiated treatment for agents of the State shall be applicable only to the Criminal Code in force at the time of the commission of the fact, any time that makes it difficult for the imputation of Crimes Against Humanity in terms of criteria of systematicity and generality, which establishes the Statute of Rome and that are subject to review of the International Criminal Court